PENGARUH PEMAHAMAN SISTEM BAGI HASIL DAN SISTEM BUNGA TERHADAP MINAT MENABUNG PADA BANK SYARIAH (Studi Kasus Mahasiswa Perbankan Syariah di Kota Pekanbaru) - Lola Amalia (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2024)
ABSTRACT This study aims to determine the influence of understanding the profit-sharing system and interest system on interest in saving in Islamic banks (a case study of Islamic banking students in the city of Pekanbaru). This type of research uses quantitative research methods. The population of this study is all Islamic banking students at Pekanbaru City College. The data collection technique used is a questionnaire. By distributing a questionnaire to 178 respondents. The method used is probability sampling with simple random sampling techniques. The results of this study show that there is a positive and significant influence between the variables of understanding the profit-sharing system on interest in saving in Islamic banks. Meanwhile, the variable of understanding the interest system on interest in saving in Islamic banks has a positive and significant effect. Then there is a positive and significant effect together between the variables of understanding the profit-sharing system and the variables of the interest system on the interest in saving in Islamic banks. This study concluded that the R Square number has a value of 55.4% of the variable dependen influenced by the variable independen, While the remaining 44.6% is determined by other variables. Keywords: Understanding the Profit Sharing System, Understanding the Interest System, Interest in Saving at Islamic Banks